Normative Values for Intertrial Variability of Motor Responses to Nerve Root and Transcranial Stimulation: A Condition for Follow-Up Studies in Individual Subjects - Troni, Walter; Melillo, Federica; Bertolotto, Antonio; Malucchi, Simona; Capobianco, Marco; Sperli, Francesca; Di Sapio, Alessia (PloS one, 2016)
Intertrial variability (ITV) of motor responses to peripheral (CMAP) and transcranial (MEP) stimulation prevents their use in follow-up studies. Our purpose was to develop strategies to reduce and measure CMAP and MEP ITV to guide long-term monitoring of conduction slowing and conduction failure of peripheral and central motor pathway in the individual patient. Maximal compound muscle action potentials to High Voltage Electrical Stimulation (HVES) of lumbo-sacral nerve roots (r-CMAP) and activated, averaged motor evoked potentials (MEPs) to Transcranial Magnetic Stimulation (TMS) using double cone coil were recorded from 10 proximal and distal muscle districts of lower limbs. The procedure was repeated twice, 1-2 days apart, in 30 subjects, including healthy volunteers and clinically stable multiple sclerosis patients, using constant stimulating and recording sites and adopting a standardized procedure of voluntary activation. ITV for latency and area indexes and for the ratio between MEP and r-CMAP areas (a-Ratio) was expressed as Relative Intertrial Variation (RIV, 5th-95th percentile). As an inverse correlation between the size of area and ITV was found, raw ITV values were normalized as a function of area to make them comparable with one another. All RIV values for latencies were significantly below the optimum threshold of ± 10%, with the exception of r-CMAP latencies recorded from Vastus Lateralis muscle. RIVs for a-Ratio, the most important index of central conduction failure, ranged from a maximum of -25.3% to +32.2% (Vastus Medialis) to a minimum of -15.0% to + 17.4% (Flexor Hallucis Brevis). The described procedure represents an effort to lower as much as possible variability of motor responses in serial recording; the reported ITV normative values are the necessary premise to detect significant changes of motor conduction slowing and failure in the individual patient in follow-up studies.